COMMUNICATIVE APPROACH TO TRAINING OF UKRAINIAN LANGUAGE AS FOREIGN LANGUAGE - Tsaryk, Olga (Mountain School of Ukrainian Carpaty, 2019)
The article examines approaches, methods, techniques, forms of teaching Ukrainian as a foreign language, the use of which helps teachers of languages to increase the level of motivation of foreign students in the process of language learning. The relevance of the chosen topic is caused by the insufficient number of studies conducted on the methodology of teaching Ukrainian as a foreign language, the need to systematize scientific and methodological developments, the need for introducing new approaches to the study of the Ukrainian language as a foreign language. The purpose of the article is to study the main approaches, methods and principles of teaching Ukrainian as a foreign language, in particular the communicative approach, the study of the influence of teaching methods on the motivation of students in the process of studying Ukrainian as a foreign language. The research uses methods of observation, questionnaires, analysis of the results of the survey, assessment of the level of proficiency in Ukrainian as a foreign language. The research was carried out at Ternopil National Economic University, where a survey of students of the preparatory department for foreign citizens, foreign students of 1-4 years of non-philology specialties was conducted. The results of the study confirmed that the main motivation for students studying Ukrainian as a foreign language is the desire to communicate freely with native speakers. Among the types of speech activities students would like to improve, the largest percentage is speech. It is revealed that the most difficult task for students is to construct sentences, reproduction of speech. The article substantiates the basic principles of the learning process, studies the influence of teaching methods on the motivation of students to study Ukrainian as a foreign language, which confirms the effectiveness of using the communicative approach in the process of teaching Ukrainian as a foreign language.